If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3y)(5x + 3y) = 0 Multiply (x + 3y) * (5x + 3y) (x(5x + 3y) + 3y * (5x + 3y)) = 0 ((5x * x + 3y * x) + 3y * (5x + 3y)) = 0 Reorder the terms: ((3xy + 5x2) + 3y * (5x + 3y)) = 0 ((3xy + 5x2) + 3y * (5x + 3y)) = 0 (3xy + 5x2 + (5x * 3y + 3y * 3y)) = 0 (3xy + 5x2 + (15xy + 9y2)) = 0 Reorder the terms: (3xy + 15xy + 5x2 + 9y2) = 0 Combine like terms: 3xy + 15xy = 18xy (18xy + 5x2 + 9y2) = 0 Solving 18xy + 5x2 + 9y2 = 0 Solving for variable 'x'. Factor a trinomial. (5x + 3y)(x + 3y) = 0Subproblem 1
Set the factor '(5x + 3y)' equal to zero and attempt to solve: Simplifying 5x + 3y = 0 Solving 5x + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 5x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 5x + 0 = 0 + -3y 5x = 0 + -3y Remove the zero: 5x = -3y Divide each side by '5'. x = -0.6y Simplifying x = -0.6ySubproblem 2
Set the factor '(x + 3y)' equal to zero and attempt to solve: Simplifying x + 3y = 0 Solving x + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 x + 0 = 0 + -3y x = 0 + -3y Remove the zero: x = -3y Simplifying x = -3ySolution
x = {-0.6y, -3y}
| (4y+2)(4-y)=0 | | 2z=1.8+0.8 | | 56=14y-7y | | (3y^2-5y+2)-(3y^6)=19 | | -0.4x=-12 | | 9n+6+5n-31=203 | | 5t^3+6t^2-10t-12=0 | | 3x-3=-3-3 | | 2-b=16 | | 3(5x+2)=3*5x+3*2 | | 1.5=3y+11.1 | | 45a+18ac=a | | 2(3x-12)=3(2x+10) | | 3n+3.1=8.2 | | 4(-2)squared+8(-2)squared+3(-2)squared+6= | | 4x+16=2(x+8) | | y=-2x-19 | | (6x+7)+(2x-3)=180 | | x+49=366 | | 35000.00+1680.00x=300.440 | | -6y^3+6y=6y^2-6 | | 64t+70t=603 | | 0=5x+35 | | 5n-5=-50 | | 6-(-9s+3)=-8s+8 | | 18-7+(-7)= | | 350=2l+2w | | 1.8=3y+15.6 | | 7-[5x+2(4x-1)]=2x-3(x+9) | | 18-6+(-5)= | | xdy+2ydx=0 | | (3xy^2+2y)dx+(3x^2y+2x)dy=0 |